Functional Analysis of the Cyclin E Gene in the Reproductive Development of Rainbow Trout (Oncorhynchus mykiss) - Enhui Liu; Haixia Song; Wei Gu; Gaochao Wang; Peng Fan; Kaibo Ge; Yunchao Sun; Datian Li; Gefeng Xu; Tianqing Huang (Biology, 2025)
As a commercially valuable aquaculture species, rainbow trout (Oncorhynchus mykiss) urgently require solutions to growth inhibition associated with reproductive development. To elucidate the function of the cell cycle regulator Cyclin E genes (CCNE1 and CCNE2) in this process, we cloned the genes and analyzed their relative expression across various tissues and gonadal developmental stages. Using RNA interference (RNAi) and overexpression in RTG2 cells, we examined the effects of CCNE on cell viability, proliferation, and meiotic gene expression. Results showed that the open reading frame lengths of CCNE1 and CCNE2 were 1230 bp and 1188 bp, encoding 408 and 395 amino acids, respectively. Both proteins contain two conserved cyclin boxes, exhibit high structural similarity, and are phylogenetically most closely related to Oncorhynchus tshawytscha and Oncorhynchus kisutch. Expression and localization analyses revealed that CCNE1 was highly expressed in the ovary, while CCNE2 was highly expressed in the testis. Both proteins were expressed during fertilized egg development and key gonadal stages (at 13, 21, and 35 months post-fertilization). CCNE expression positively correlated with RTG2 cell viability and proliferation, with immunofluorescence confirming that CCNE is localized in the nucleus. Knockdown or overexpression of CCNE induced the differential expression of reproductive-related genes and key meiotic regulators. These findings suggest that CCNE1 and CCNE2 balance meiosis and gamete development through specific regulatory mechanisms, and their dysregulation may be a key factor underlying meiosis inhibition and reproductive development abnormalities.